A Survey of Licensed Acupuncturists in the San Francisco Bay Area: Prevalence of Treating Oncology Patients. (March 2018) - Abrams, Donald; McCulloch, Michael; Cohen, Misha; Liaw, Mike; Silverman, Deborah; Wilson, Carla
Background: Many cancer patients seek traditional Chinese medicine (TCM), the prevalence varying with diagnosis, comorbidities, and demographics. Interventions sought include acupuncture, massage, herbs, diet, and exercise, usually combined with conventional therapies. It is not known what proportion of TCM practitioners care for cancer patients, their cancer specific training or caseload, what interventions they employ, their outcomes, and their communication patterns with conventional oncologists.Methods: A survey was mailed to all 2213 licensed acupuncturists in the 9-county San Francisco Bay Area gathering descriptive statistics.Results: A total of 472 (21%) responded by mail or web-based Research Electronic Data Capture (REDCap) tool. Most respondents (77%) reported caring for patients with cancer, with 29% reporting having 6 to 10 years of practice experience, and 44.2% having 0 to 20 hours of training specific to the needs of patients with cancer. Improving quality of life was reported by 94% as what their treatment offered cancer patients as well as the area where treatment was felt to have the greatest impact. The most useful TCM modalities were acupuncture (98%), herbs (79%), diet (72%), moxibustion (46%), and meditation instruction (44%). Absence of adverse reactions was noted by 95%. Ninety-one percent reported "never" or "hardly ever" having been contacted by patients' oncologists to discuss treatment.Conclusions: Many acupuncturists seeing cancer patients have significant clinical experience and have sought specialized training. Improved communication is needed between TCM practitioners and oncologists sharing care of cancer patients.